Neurocognitive functioning, clinical course and functional outcome in first‐treatment bipolar I disorder patients with and without clinical relapse: A 1‐year follow‐up study. (9th November 2017) - Demmo, Christine; Lagerberg, Trine V; Kvitland, Levi R; Aminoff, Sofie R; Hellvin, Tone; Simonsen, Carmen; Haatveit, Beathe; Andreassen, Ole A; Melle, Ingrid; Ueland, Torill
Abstract : Objectives: Due to limited research on the association between recurrence of mood episodes and the longitudinal course of neurocognitive functioning in early phase bipolar I disorder (BD I), the impact of recurrence on neurocognition remains unclear. Further, a strong correlation between neurocognitive impairment and functional impairment has been demonstrated. The longitudinal relationship between neurocognitive impairment and functional outcome in relation to recurrence is, however, not established. Methods: The current study investigated the longitudinal relationship between neurocognition, recurrence of mood episodes and functional outcome in a sample of first‐treatment (FT) BD I patients (N = 42), with and without relapse, during a 1‐year follow‐up period. The longitudinal course of neurocognitive functioning in the patients was also compared to that of a group of healthy controls (N = 143). Results: Compared to both patients with relapse and healthy controls, no‐relapse patients showed neurocognitive improvements. The polarity of the relapse episodes was mostly depressive, and for the no‐relapse patients, reduction of symptoms was associated with neurocognitive improvement. No‐relapse patients showed better global and occupational functioning. Conclusions: The current study found different neurocognitive and functional trajectories in FT BD I patients with and without relapse, with differences at follow‐up to some degree being mediated by current symptoms. The current findings highlight the importance of treatment focusing on neurocognition and symptom states with the aim of improving functional recovery.